Prospects for the Detection of High-redshift Gamma-Ray Bursts in the Era of EP and SVOM - Jun-Jie Wei; Xue-Feng Wu (The Astrophysical Journal Letters, 2025)
Gamma-ray bursts (GRBs) are a promising probe of the high-redshift Universe, but their detection remains observationally challenging. In this work, we explore the detectability of high- z GRBs by the Wide-field X-ray Telescope (WXT) on board the Einstein Probe (EP) and the coded-mask gamma-ray imager (ECLAIRs) on board the Space-based multi-band astronomical Variable Objects Monitor (SVOM). Using a population synthesis model calibrated to Swift GRB observations, we develop a tool to estimate high- z GRB detection rates for instruments with specific energy bands and sensitivities. Our results indicate that EP/WXT could detect $\sim 5.{1}_{-2.4}^{+3.4}$ (with 68% confidence level) GRBs annually at z  > 6, compared to $\sim 0.{7}_{-0.4}^{+1.0}$ events per year at z  > 6 for SVOM/ECLAIRs. While EP cannot independently determine redshifts (requiring optical/near-infrared, NIR, follow-up), its assumed ∼30% follow-up efficiency yields $\sim 1.{5}_{-0.7}^{+1.0}$ confirmed z  > 6 GRBs annually. SVOM, equipped with dedicated follow-up telescopes, will promptly identify high- z candidates deserving deep NIR spectroscopy to ensure robust confirmation of high- z GRBs. We anticipate that EP and SVOM will open new avenues for utilizing enlarged samples of high- z GRBs to explore the early Universe. Moreover, EP will assemble a substantial sample of soft, low-luminosity GRBs at low-to-intermediate redshifts, providing critical insights into the structure of GRB jets.